Sharing an experience: field study methods to understand management accounting practices in a changing environment / Sujatha Perera - Perera, Sujatha (Accounting Research Institute (ARI) & Faculty of Accountancy, 2005)
Concerns have been expressed about the small number of publications of field based accounting research in top ranking journals. The limited understanding of how to conduct high quality field based research in accounting has been noted as a contributing factor for both the low publication rate and the reluctance of researchers to undertake field-based research. This paper reports how field study method has been applied to address a research question in management accounting area. The paper describes the procedures that were followed to collect and analyse data, and the measures taken to address threats to validity and reliability of the study. The paper also discusses, in hindsight, the ways in which the quality of the procedures adopted in the study could have been improved. Those researchers who are interested in applying field study method will particularly benefit from this paper as it provides insights into the: (a) strengths, limitations and difficulties associated with field study methods; (b) procedures that may be followed when using field study methods to address a research question similar to the one discussed in the paper; and (c) the pitfalls to be avoided and the factors that need careful consideration when conducting field based research.